Outpatient Error in Perception of Medication; is it a Miscommunication Problem? - J, Zainah; I, Marina; A, Asrina; M, Kanmani; A, Asma’ (IIUM Medical Journal Malaysia, 2020)
Introduction: The NCC for Medication Error defines it as any preventable event that may lead to inappropriate medication use or patient harm while the medication is in control of the healthcare professionals, patients or consumers. The annual cost of drug related morbidity and mortality is US 177 billion in America. The FDA states that one death per day and 1.3 million people were injured yearly due to medication error. The objectives of this study were to comply with patients’ safety goals, to achieve zero medication error and to ensure compliance among outpatients.Materials and Methods: All outpatients’ prescriptions were analyzed prospectively from January to December 2009. The data were categorized according to incomplete prescription, inappropriate drug regimen, illegibility and wrong administration to patients. We introduced a coloured labeling system to improve patient understanding of medication administration routes and frequency. Results: Data analysis between January and May 2009 showed medication error in outpatients was high. By doing root-cause analysis, we identified the main cause of medication error was miscommunication between pharmacist and outpatients. To correct this error, visual reinforcement on the routes of administration was done to enable patients to better understand the right administration of medications. From June to October 2009 post implementation showed reduction of medication error from 1.34% to 0.82%. Zero medication error was achieved in the last two months. Feedback from patients revealed that 88.2% agreed poor labeling was the main cause of wrong administration of drugs at home. Conclusion: Although studies had been done on inpatient medication errors, we had no data over outpatients’ prescription trends. Although this study was simple, yet by creating multi-colored labels which were user friendly we have shown that outpatients’ medication error can be rectified.